Analysis of meteorological droughts in the Sonora river basin, Mexico - Hernández Vásquez, Claudio César; Ibáñez Castillo, Laura Alicia; Gómez Díaz, Jesús David; Arteaga Ramírez, Ramón (Atmósfera, 2022)
ABSTRACT Drought is a complex natural hazard that has numerous negative effects on ecosystems, agriculture, and the economy. For this reason, it is difficult to provide a precise definition. Nevertheless, different conceptualizations converge in one common denominator: the deficit of precipitation with respect to an average historical value. Droughts in Mexico have been recurrent and persistent, resulting from complex interactions of the atmosphere with the oceans and the geographic and physiographic characteristic of the country. Several researchers have approached this phenomenon with indices to characterize it using features such as intensity, duration and frequency. In this study we analyze droughts in a spatiotemporal context at scales of 3, 6, 12 and 24 months with SPI and SPEI indices at 19 weather stations located in middle and upper regions of the Sonora River basin, Mexico, for the period 1974-2013. The regions were defined according to mean annual rainfall behavior, applying statistical techniques and analyzing the physiographic characteristics of the study region. Results indicate that drought intensity increased at the end of the time series analyzed, and important periods were identified in the years 1997, 1999, 2000 and 2011 to 2013. SPEI defined the drought periods and the increasing intensity trend better than SPI, demonstrating the importance of including variables such as evapotranspiration in the balance of available water.